Sinergisitas Sikap dan Pengetahuan dalam Pengembangan Jiwa Kewirausahaan Mahasiswa Febi IAIN Bukittinggi - Harfandi Harfandi; Era Sonita (EKONOMIKA SYARIAH : Journal of Economic Studies, 2020)
The objective of this research to analysis deeply examine the synergy of attitude and knowledge to develop entrepreneurship spirit of the students of Faculty of Economics and Islamic Business (FEBI) IAIN Bukittinggi. After analyzed qualitatively using; SWOT analysis, SWOT Matrix, and Charge Table Score, it can be pointed out that the synergy of attitude and knowledge in the development of entrepreneurship of students namely; 1) To grow values: honesty, tolerance,  ideas and creativity, awareness of the norms and rules, a strong spirit in learning, a strong drive to excel, confidence, and independence, interest, perseverance, and motivation, the desire to explore and produce economic resources, entrepreneurial spirit and entrepreneurship, And, 2). Realizing knowledge about; entrepreneurship ideas that suits the needs of the market, the development of business prospects, and business management. This research contributed to prepare the graduates who can compete in both academic and non-academic fields